Landscape care of urban vacant properties and implications for health and safety: Lessons from photovoice. (July 2017) - Sampson, Natalie; Nassauer, Joan; Schulz, Amy; Hurd, Kathleen; Dorman, Cynthia; Ligon, Khalil
Abstract: Care of vacant properties in urban environments is of particular interest to planners and residents alike. We report on a photovoice project completed by community leaders, researchers, and residents in two Detroit neighborhoods experiencing longtime systemic disinvestment. Participants photographed and discussed examples of care in a series of three focus groups in each neighborhood. Analyses highlight how acts of landscape care and visible cues to care contribute to changes in physical and social environments, and explore various links to health. We suggest theoretical and practical applications of residents' perspectives on landscape care and identify implications for well-being and neighborhood stability. Highlights: Within disinvested urban neighborhoods, burden of landscape care is high. Cues to care may reduce injury and stress and increase perceived safety. Acts of care may increase physical activity and be a stressor or coping mechanism. Individual and organized acts of care may build and strengthen social networks. Government acts of care may overlook or counteract neighborhood-led efforts.